Method of Preparation for Technical Actions of Greco-Roman Wrestlers (Eurasian Scientific Herald, 2022)
The article explains how young Greco-Roman wrestlers need to be taught the technique. Teaches young Greco-roman wrestlers the technique of modeling their training techniques. Learn how to increase the effectiveness of using young Greco-Roman wrestlers in the training process.